2015
DOI: 10.1149/2.0021512jss
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Method for Determining Combination of Organic Compounds Interacting with Each Other on Silicon Oxide Surface

Abstract: An experimental process for determining a combination of organic compounds, interacting with each other on a silicon oxide surface, was developed using a quartz crystal microbalance. The surface concentration of the four organic compounds, such as L-menthone (Mth), decylacetate (DA), diethylphthalate (DEP) and octanol (OCT), on a silicon oxide surface was evaluated in multi-component systems. The increase and decrease in the surface concentrations were not reversible with the changing gas phase concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Because the QCM frequency value was taken after the sufficiently long supply of the DEP and Mth, such as that longer than 120 s, the behavior at 25 °C showed that the surface concentration behavior was irreversible and similar to a previous study. 9 The surface concentrations at Conditions B, C and D at 25 °C in Fig. 11c were larger than those in Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Because the QCM frequency value was taken after the sufficiently long supply of the DEP and Mth, such as that longer than 120 s, the behavior at 25 °C showed that the surface concentration behavior was irreversible and similar to a previous study. 9 The surface concentrations at Conditions B, C and D at 25 °C in Fig. 11c were larger than those in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…This behavior was the same as that in the previous study. 9 Next, the surface concentration was measured after the DEP vapor was supplied without the Mth vapor. Figures 11a and 11b show that the DEP concentration was 2.7 ng cm −3 while the Mth concentration was zero ng cm −3 under Condition A and at the temperature of 25 °C.…”
Section: Resultsmentioning
confidence: 99%